You should evaluate the limit of the function `e^x` under the given condition, such that:

`lim_(x->-oo) e^x = e^(-oo)`

Using negative power property yields:

`a^(-b) = 1/a^b`

Reasoning by analogy yields:

`e^(-oo) = 1/e^oo = 1/oo = 0`

** Hence, evaluating the limit of the given function `e^x` , under the given...**

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should evaluate the limit of the function `e^x` under the given condition, such that:

`lim_(x->-oo) e^x = e^(-oo)`

Using negative power property yields:

`a^(-b) = 1/a^b`

Reasoning by analogy yields:

`e^(-oo) = 1/e^oo = 1/oo = 0`

**Hence, evaluating the limit of the given function `e^x` , under the given conditionsm, yields `lim_(x->-oo) e^x = 0.` **